PENGARUH JENIS BAHAN PERENDAM TERHADAP KARAKTERISTIK KERIPIK KETELA UNGU (Ipomoea batatas) - Lailatun Najja, Hannik; Admadi H, Bambang; Lani Triani, I. Gusti Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September)
This studied aims to determine the effect of various types of immersion on the characteristics of purple sweet potato chips and determines the specific type of immersion will produce the best purple sweet potato chips. This experiment used a randomized block design (RBD) using 4 types of immersion is 0.1% CaCl2, 0.1% baking powder, 0.1% Na metabisulphite, water. Each treatment except water dissolved in 2 liters of water and stirred until homogeneous then grouped into 4 time process in order to obtain 16 units experiment. Data were analyzed by analysis of variance followed by Duncan test. The results of this study are the various type of immersion material effect on moisture content, ash content, and the anthocyanin content of the purple sweet potato chips sensory properties (color, aroma, flavor, texture, and overall acceptance). Characteristics of purple sweet potato chips are best obtained in the treatment of immersion Na metabisulphite type material with 5.14% moisture content, ash content of 3.97%, 0.542% anthocyanins levels. For sensory properties, color 5,35 (rather like), aroma 5.00 (rather like), taste 6,05 (like), texture 5.95 (like) and overall acceptance 5.95 (like).
Keywords: 53,